Abandoned in death [compact disc, unabridged] - Robb, J. D., 1950- (Robb, J. D., 1950- In death novel., 2022)
"Homicide detective Eve Dallas races to untangle a twisted family history while a hostage's life hangs in the balance--in the new In Death novel by New York Times bestselling author J.D. Robb"--